Conditional change of DNA replication control in an RNA polymerase mutant of Escherichia coli. - Rasmussen, K V (1983)
A temperature-sensitive mutant of Escherichia coli with a temperature-dependent change in the control of initiation of DNA replication was isolated. The phenotype of the mutant was dependent on a mutation in the RNA polymerase gene rpoC. In vitro RNA polymerase activity was temperature sensitive. The mutant grew and synthesized DNA at 30 degrees C as did the wild type. After a shift to 39 degrees C, a temperature still permissive for growth, the mutant increased its origin concentration more than twofold. After a shift from 39 to 30 degrees C, initiation of DNA replication was inhibited until the normal origin concentration was reestablished.